Rapidly Growing and Recurrent Pumonary Venous Leiomyosarcoma Involving the left Atrium: Detected by Echocardiography with its Fatal Consequences - A Case Report - Biswas, SK; Hishida, Hitoshi; Kimura, Miyuki; Sugimoto, Kunihiko; Iwase, Masatsugu (Journal of Bangladesh College of Physicians and Surgeons, 2007)
(J Bangladesh Coll Phys Surg 2006; 24 : 122-126)